Electronic structure and ferromagnetism of polycrystalline Zn1-xCoxO (0 <= x <= 0.15) - Deka, Sasanka; Joy, Pattayil Alias (Solid State Communications, 2005)
The electronic structure of polycrystalline ferromagnetic Zn1-x,CoxO (0.05 <= x <= 0.15) and the oxidation state of Co in it, have been investigated. The Co-doped polycrystalline samples are synthesized by a combustion method and are ferromagnetic at room temperature. XPS and optical absorption studies show evidence for Co2+ ions in the tetrahedral symmetry, indicating, substitution of Co2+ in the ZnO lattice. However, powder XRD and electron diffraction data shock the presence of Co metal in the samples. This give evidence to the fact that some Co2+ ion are incorporated in the ZnO lattice which gives changes in the electronic structure whereas ferromagnetism comes from the Co metal impurities present in the samples. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Magnetically ordered materials; Optical properties; Semiconductors

High magnetic aspects of nanosized NiZn ferrite powders synthesized by an autocombustion method - Deka, Sasanka; Date, Sadgopal K.; Joy, Pattayil Alias (9th International Conference on Ferrites (ICF-9), 2005)
Nanocrystalline NiZn ferrite, Ni0.5Zn0.5Fe2O4, having particle size in the range 6-10 mn, has been synthesized by an auto-combustion method. The nanosized ferrite powder formed at a low temperature is annealed at different temperatures in the range 473-1273 K and characterized by X-ray diffraction, vibrating sample magnetometry, Mossbauer spectroscopy, transmission electron microscopy and scanning electron microscopy. Magnetic transition temperature broadening up to 773 K is observed for the nanosized sample, compared to the T-c = 563 K for the bulk material. Critical particle diameter (D-c) is found to be similar to 40 nm at which maximum coercivity is obtained for the powder sample annealed at 973 K. Similarly, high room temperature magnetization, comparable to that of the bulk material, is obtained for the powders annealed at 1073 K, with a maximum particle size of similar to 50 nm. Very little grain growth is observed for the powders annealed above 1073 K. The results show that, optimum magnetic properties can be achieved for fine particle NiZn ferrite powders synthesized by a low-temperature auto-combustion method and processed at relatively lower temperatures.

Synthesis and magnetic properties of polycrystalline Co-doped ZnO - Deka, Sasanka; Date, Sadgopal K.; Joy, Pattayil Alias (9th International Conference on Ferrites (ICF-9), 2005)
Nanocrystalline Zn1-xCoxO powders have been synthesized by a glycine-nitrate (GNP) and modified GNP methods. Ferromagnetism at room temperature and above is observed for the powder samples synthesized by GNP method. The saturation magnetization value at 300 K is obtained as 0.08 and 0.28 emu/g (at 1 T), respectively, for x = 0.05 and 0.1. Ferromagnetic transition occurs at 740 K and 770 K for the respective samples, which is much larger than that the reported in the literature for thin film samples. On the other hand, no ferromagnetism was observed, down to 10 K, for the compounds synthesized by the modified GNP method.

Characterization of nanosized NiZn ferrite powders synthesized by an autocombustion method - Deka, Sasanka; Joy, Pattayil Alias (Materials Chemistry and Physics, 2006)
Nanocrystalline Ni0.5Zn0.5Fe2O4 with average particle size of similar to 9 nm has been synthesized by an autocombustion method and characterized by powder XRD, TEM and room temperature magnetic measurements. High room temperature magnetization comparable to that of the bulk material is obtained for the nanosized powders annealed at 800 degrees C, with a maximum particle size of similar to 54 nm. The results show that optimum properties can be achieved for NiZn ferrite powders synthesized by the present autocombustion method and processed at relatively lower temperatures. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Magnetic materials; magnetic properties; Oxides

Experimental comparison of the structural, magnetic, electronic, and optical properties of ferromagnetic and paramagnetic polycrystalline Zn1-xCoxO (x=0,0.05,0.1) - Deka, Sasanka; Pasricha, Renu; Joy, Pattayil Alias (Physical Review B, 2006)
Ferromagnetism at room temperature is observed in one case whereas paramagnetism down to 12 K is observed in the second case when polycrystalline Zn1-xCoxO is synthesized under almost identical conditions. Identical x-ray diffraction, optical absorption, and x-ray photoelectron spectroscopy results indicate the incorporation of Co2+ ions in the ZnO lattice in both cases. However, electron diffraction studies show the presence of Co metal impurities in the ferromagnetic samples, indicating that pure Co doped ZnO is not likely to be ferromagnetic.

Ferromagnetism induced by hydrogen in polycrystalline nonmagnetic Zn0.95Co0.05O - Deka, Sasanka; Joy, Pattayil Alias (Applied Physics Letters, 2006)
Polycrystalline Zn0.95Co0.05O is found to be paramagnetic at room temperature and down to 12 K. Optical measurements prove the incorporation of Co2+ ions inside the ZnO lattice in the tetrahedral site. When the paramagnetic sample is heated in Ar/H-2 at 1125 K for 2 h, ferromagnetism with a very high value of magnetization is observed at room temperature. Hydrogen reduction does not affect the substituted Co2+ ions inside the wurtzite crystal lattice as evidenced from optical studies. X-ray diffraction studies show the presence of Co metal after the reduction process which is the origin of room temperature ferromagnetism. (c) 2006 American Institute of Physics.

Size-dependent magnetic properties of nanocrystalline yttrium iron garnet powders - Rajendran, M.; Deka, Sasanka; Joy, Pattayil Alias; Bhattacharya, Asish K. (Journal of Magnetism and Magnetic Materials, 2006)
Yttrium iron garnet (YIG) powders with particle sizes of 9, 14, 25 and 60 nm have been synthesised and their magnetic properties have been studied as a function of particle size and temperature. The particles with sizes of 9 and 14 nm exhibited superparamagnetism. The blocking temperature (T-B) decreased with decreasing particle size, whereas the anisotropy constant (K) increased. The saturation magnetisation (M-s) decreased with decreasing particle size. These variations are attributed to large surface-to-volume ratios in nanoparticles where the surface moments are predominant. (c) 2005 Published by Elsevier B.V.
Keywords: anisotropy constant; Magnetism; Nanoparticles; Superparamagnetism; YIG

Enhanced permeability and dielectric constant of NiZn ferrite synthesized in nanocrystalline form by a combustion method - Deka, Sasanka; Joy, Pattayil Alias (Journal of the American Ceramic Society, 2007)
The performance parameters of Ni0.5Zn0.5Fe2O4, synthesized in the nanocrystalline form by an autocombustion method, have been investigated. The sample sintered at 1200 degrees C, with Bi2O3 as additive shows a very high value of initial permeability mu'(i) of > 400 at 1 MHz, with low loss. Similarly, a very high dielectric constant is obtained at lower frequencies. The results show that optimum magnetic and electrical properties can be achieved for the NiZn ferrite nanocrystalline powders synthesized by the present autocombustion method and sintered at a relatively lower temperature of 1200 degrees C when compared with a temperature of 1400 degrees C required for the materials synthesized by the conventional ceramic method.

Enhancement of the phase transformation temperature of gamma-Fe2O3 by Zn2+ doping - Deka, Sasanka; Joy, Pattayil Alias (Journal of Materials Chemistry, 2007)
The phase transformation temperature of gamma-Fe2O3 to alpha-Fe2O3 is increased with Zn2+ doping and enhancement of the transition temperature by similar to 100 degrees C is obtained for doping of >= 15 mol% Zn in nanocrystalline gamma-Fe2O3 synthesized by an autocombustion method.

Synthesis and magnetic properties of Mn doped ZnO nanowires - Deka, Sasanka; Joy, Pattayil Alias (Solid State Communications, 2007)
Mn doped ZnO nanowires have been synthesized using a simple autocombustion method. The as-synthesized Mn doped ZnO nanowires were characterized by X-ray diffraction and transmission electron microscopy. An increase in the hexagonal lattice parameters of ZnO is observed on increasing the Mn concentration. Optical absorption studies show an increment in the band gap with increasing Mn content, and also give evidence for the presence of Mn2+ ions in tetrahedral sites. All Zn1-xMnxO (0 <= x <= 0.25) samples are paramagnetic at room temperature. However, a large increase in the magnetization is observed below 50 K. This behavior, along with the negative value of the Weiss constant obtained from the linear fit to the susceptibility data below room temperature, indicate ferrimagnetic behavior. The origin of ferrimagnetism is likely to be either the intrinsic characteristics of the Mn doped samples, or due to some spinel-type impurity phases present in the samples that could not be detected. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Combustion synthesis; diluted magnetic semiconductor; magnetic properties; Mn doped ZnO

Magnetic and Mossbauer spectroscopic studies of NiZn ferrite nanoparticles synthesized by a combustion method - Sreeja, V.; Vijayanand, S.; Deka, Sasanka; Joy, Pattayil Alias (Hyperfine Interactions, 2008)
The properties of nanocrystalline Ni(0.5)Zn(0.5)Fe(2)O(4) synthesized by an auto-combustion method have been investigated by magnetic measurements and Mossbauer spectroscopy. The as-synthesized single phase nanosized ferrite powder is annealed at different temperatures in the range 673-1,273 K to obtain nanoparticles of different sizes. The powders are characterized by powder X-ray diffraction, vibrating sample magnetometer, transmission electron microscopy and Mossbauer spectroscopy. The as-synthesized powder with average particle size of similar to 9 nm is superparamagnetic. Magnetic transition temperature increases up to 665 K for the nanosized powder as compared to the transition temperature of 548 K for the bulk ferrite. This has been confirmed as due to the abnormal cation distribution, as evidenced from room temperature Mossbauer spectroscopic studies.
Keywords: Ferrite; magnetic properties; Mossbauer spectroscopy; Nanoparticles

Studies on ZnO based diluted magnetic semiconductors - Deka, Sasanka; Joy, P. A. (TMS 2008 Annual Meeting Supplemental Proceedings, 2008)
The observation of ferromagnetism in the transition metal (TM) doped wide band gap nonmagnetic semiconductor ZnO opened up a new area of research because of the potential applications in spintronics devices. These ZnO based diluted magnetic semiconductors (DMS) combine their transport and optical properties with magnetism. We have carried out synthesis and studies on the magnetic and optical properties on TM doped ZnO powders in nanocrystalline form. Our studies give evidence for the origin of ferromagnetism as extrinsic due to the presence of metal nanoclusters as secondary phases in the Co and Ni doped ZnO systems although the optical and electronic structure studies indicate the incorporation of divalent metal ions inside the ZnO crystal lattice.

Superparamagnetic nanocrystalline ZnFe2O4 with a very high curie temperature - Deka, Sasanka; Joy, Pattayil Alias (Journal of Nanoscience and Nanotechnology, 2008)
Studies on the magnetic properties of nanocrystalline ZnFe2O4 synthesized by an autocombustion method are reported. Superparamagnetic behavior is observed for the nanocrystalline materials with particle sizes of 8 nm and 17 nm, with superparamagnetic blocking temperatures of 65 K and 75 K, respectively. Magnetic hysteresis with very large coercivities of 533 Oe and 325 Oe, respectively, are observed at 12 K. Studies on the temperature variation of the magnetization above room temperature indicate that the Curie temperature is as high as similar to 800 K when compared to the paramagnetic nature of bulk zinc ferrite at room temperature.
Keywords: Curie temperature; Nanocrystalline; Superparamagnetism; Zinc Ferrite

Single step synthesis and properties of M/MFe2O4 and PVDF/M/MFe2O4 (M = Co, Ni) magnetic nanocomposites - Deka, Sasanka; Joy, Pattayil Alias; Kumar, A. Pratheep (Science of Advanced Materials, 2009)
Metal/ferrite nanocomposites (M/MFe2O4; M = Co, Ni), consisting of nanoparticles of a metal and the corresponding metal ferrite, have been synthesized under in situ conditions by a simple and single step process. The metal/ferrite nanocomposites embedded in a polymer matrix have been prepared by a simple hot-pressing method. The performance parameters such as magnetization, coercivity, permeability and dielectric constant of the two- and three-phase nanocomposite systems are compared. The coercivity increases and the permeability decreases with increasing polymer content in the three-phase composite. Enhancement of the dielectric constant is observed at low frequencies.
Keywords: Dielectric; Ferrite; magnetic properties; Nanocomposite; Nanocrystalline; permeability

Preferential growth of Au on CdSe quantum dots using langmuir-blodgett technique - Das, Subhasis; Satpati, Biswarup; Chauhan, Himani; Deka, Sasanka; Gopinath, Chinnakonda S.; Bala, Tanushree (RSC Advances, 2014)
Oleyl amine capped CdSe quantum dots (QD) were synthesised by hot injection technique. These QDs formed a self-assembled monolayer on an aqueous subphase of a Langmuir-Blodgett (LB) trough. Here, in this report we introduced a simple but very efficient route to form a metal (Au)-QD hybrid nanostructure via the LB technique. In this method, the metal counterpart of the hybrid nanostructure could be deposited exclusively on one side of the QDs. The formation of stable monolayer of QDs was evidenced from a surface pressure-area (P-A) isotherm. The development of gold tip was confirmed and monitored by detailed TEM study on the monolayer deposited on TEM grids from the LB trough. Other characterizations like UV-Vis spectroscopy, FTIR, XPS and EDX also suggested the same. Oleyl amine was shown to act both as a reducing agent as well as a capping agent in this strategy.

Exploration of magnetically separable Ag@AgxNiy core/graded-alloy-shell nanostructures - Kumar, Mukesh; Soni, Kiran; Satpati, Biswarup; Gopinath, Chinnakonda S.; Deka, Sasanka (Chemical Communications, 2016)
We report novel bimetallic Ag@AgxNiy core@graded-alloy-shell nanoparticles (CGAS NPs), i.e. single Ag core NPs shelled by an AgxNiy graded alloy and stabilized by the CTAB surfactant employing a novel synthesis method. These Ag@AgxNiy CGAS NPs demonstrated superior catalytic performance in the synthesis of biologically active 3-amino alkylated indoles under green conditions.

Seeding of Au on CdSe/CdS nanoplates using Langmuir-Blodgett technique - Das, Subhasis; Satpati, Biswarup; Chauhan, Himani; Deka, Sasanka; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (RSC Advances, 2016)
Oleyl amine capped CdSe/CdS nanoplates were synthesized by hot injection technique which formed a stable monolayer over both a water subphase and an aqueous HAuCl4 subphase using a Langmuir-Blodgett trough. Au islands were generated at the edge as well as on one specific surface of the flat nanoplates by exploiting the reducing capacity of oleyl amine to form Au nanoseeds from AuCl4- ions. The initial Au nanoseeds changed to a shell surrounding these nanoplates on prolonged exposure to the subphase containing the Au precursor. Monolayer of the hybrid structures was deposited onto suitable substrates for characterization by a number of different techniques and to study the photocatalytic activity. The same substrate with the monolayers could be re-used in several cycles of photocatalysis.

Copper Cobalt Sulfide Nanosheets Realizing a Promising Electrocatalytic Oxygen Evolution Reaction - Chauhan, Meenakshi; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S.; Deka, Sasanka (ACS Catalysis, 2017)
Nanostructured CuCo2S4, a mixed metal thiospinel, is found to be a benchmark electrocatalyst for oxygen evolution reaction (OER) in this study with a low overpotential, a low Tafel slope, a high durability, and a high turnover frequency (TOF) at lower mass loadings. Nanosheets of CuCo2S4 are realized from a hydrothermal synthesis method in which the average thickness of the sheets is found to be in the range of 815 nm. Aggregated nanosheets form a highly open hierarchical structure. When used as an electrocatalyst, CuCo2S4 nanosheets offer an overpotential value of 310 mV at a 10 mA cm(2) current density, which remains consistent for 10000 measured cycles in a 1 M KOH electrolyte. A chronoamperometric study reveals constant oxygen evolution for 12 h at a 10 mV s(-1) scan rate without any degradation of the activity. Furthermore, the calculated mass activity of the CuCo2S4 electrocatalyst is found to be 14.29 A/g and to afford a TOF value of 0.1431 s(-1) at 310 mV at a mass loading of 0.7 mg cm(-2). For comparison, nanostructures of Co3S4 and Cu0.5Co2.5S4 have been synthesized using a similar method followed for CuCo2S4. When compared to the OER activities among these three thiospinels and standard IrO2, CuCo2S4 nanosheets offered the highest OER activities at the same mass loading (0.7 mg/cm(-2)). Extensive X-ray photoelectron spectroscopy and electron paramagnetic resonance analyses for a mechanistic study reveal that introduction of Cu into the Co3S4 lattice enhances the oxygen evolution and kinetics by offering Cu2+ sites for utilitarian adsorption of OH, O, and OOH reactive species and also by offering a highly active high-spin state of octahedral Co3+ for OER catalysis.
Keywords: Bifunctional Electrocatalyst; Catalyst; Cuco2s4; Efficient Electrocatalyst; electrocatalyst; Electronic-structure; Nanoparticles; Nanosheet; oxide; oxygen evolution; performance; Recent Progress; Water oxidation; Water Splitting Hydrogen Evolution

Deposition of Au nanoparticles inside porous CeO2 nanocubes using Langmuir-Blodgett technique - Das, Subhasis; Bhattacharjee, Gourab; Satpati, Biswarup; Kumar, Mukesh; Deka, Sasanka; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (New Journal of Chemistry, 2018)
Porous 3D CeO2 nanocubes were synthesized using hot injection technique. These nanocubes were able to form a stable monolayer over water and HAuCl4 subphase in Langmuir-Blodgett (LB) trough due to the presence of surface capped oleic acid and oleylamine. CeO2-Au nanocomposites were synthesized exploiting the ability of oleylamine to reduce AuCl4 ions to Au-0, via LB method. CeO2 nanocubes gave rise to excellent long-range assembly at air/water interface and gold nanoparticles were formed inside these porous nanocubes without disturbing this arrangement. The formation of a stable monolayer was evidenced from the surface pressure-area (P-A) isotherm. The development of Au nanoparticles was confirmed with great effort from a comprehensive study using UV-Vis spectroscopy, XRD, XPS, FTIR, TEM, STEM, EDX, tomography and chemical mapping.

Direct thermal polymerization approach to N-rich holey carbon nitride nanosheets and their promising photocatalytic H-2 evolution and charge-storage activities - Antil, Bindu; Kumar, Lakshya; Reddy, K. P.; Gopinath, C. S.; Deka, Sasanka (ACS Sustainable Chemistry & Engineering, 2019)
Energy conversion and energy storage are two crucial challenges in green chemistry that have attracted tremendous attention for the last several decades. In this work, we have addressed both issues by synthesizing nitrogen-rich, few-layer-thick holey graphitic carbon nitride (g-C3N4) nanosheets by a simple, novel, direct thermal polymerization method, which is found to be very good in photocatalytic H-2 evolution reaction (energy-conversion) and charge-storage supercapacitor (energy-storage) applications. This as-synthesized conjugated polymer semiconductor (obtained stoichiometry C3N4.8) with unique structural and morphological advantages exhibits superior photocatalytic water splitting activity to H-2 evolution (2 620 mu mol h(-1) g(-1)) without the help of any cocatalysts under visible light in the presence of 20% triethanolamine (TEOA). The calculated apparent quantum yield is 8.5% at 427 nm, and the rate of photocatalytic hydrogen generation remained constant for nine consecutive catalytic cycles (9 h photocatalysis). The present material also shows electrochemical double layer capacitor (EDLC) behavior in alkaline electrolyte, where a symmetric coin cell device consisting of this electrode material without any large area support or conductive filler delivers high specific capacitance (275 F g(-1)), energy density (30 Wh kg(-1)), and power density (6651 W kg(-1)), and the supercapacitor cell can retain >98% capacitance efficiency up to 10 000 measured cycles at various current densities.
Keywords: g-C3N4; Hydrogen evolution; nanosheets; Photocatalyst; supercapacitor; water splitting

Promising visible-light driven hydrogen production from water on a highly efficient CuCo2S4 nanosheet photocatalyst - Chauhan, Meenakshi; Soni, Kiran; Karthik, P. E.; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S.; Deka, Sasanka (Journal of Materials Chemistry A, 2019)
Here we report the development of CuCo2S4 nanosheets (NSs) as a promising semiconductor photocatalyst for the first time for water splitting reactions under visible light ( 420 nm) conditions, without the support of any noble metal co-catalyst. These NSs were produced via a simple hydrothermal route and have desirable properties with a band gap of 2.24 eV, and are photo-catalytically active under visible light with an apparent quantum yield (AQY) of 2.48%. Under visible light, CuCo2S4 NSs exhibit excellent weight-normalized photoactivity that generates approximate to 25900 mol h(-1) H-2 for 1 g of material with sulphide + sulphite as the sacrificial agent under 7.68 mW cm(-2) illumination, which is the best evolution reported for any chalcogenide semiconductor material without any co-catalyst to date with unprecedented long-term operational stability (up to 12 h study time). The rate and number of hydrogen gas molecules produced are 8.2855 x 10(15) s(-1) cm(-2) which remained constant for three catalytic cycles with a turnover frequency (TOF) value of 0.017 s(-1). The effect of Cu substitution on photoactivity was also investigated for comparative studies and it was found that CuCo2S4 NSs show superior activity to Cu0.5Co2.5S4 and Co3S4. These CuCo2S4 NSs absorb the entire visible range of the spectrum from 420 to 800 nm, and have a highly populated density of states at the Fermi level and a high donor concentration of 7.22 x 10(18) cm(-3) which have been evaluated by Mott-Schottky analysis and favourable adsorption of H+ on S-sites and conversion to H-2 corroborate their efficient photocatalytic activity.

Directed holey and ordered g-C(3)N(4.5)nanosheets by a hard template nanocasting approach for sustainable visible-light hydrogen evolution with prominent quantum efficiency - Antil, Bindu; Ranjan, Ravi; Gopinath, Chinnakonda S.; Deka, Sasanka (Journal of Materials Chemistry A, 2020)
It is desirable yet challenging to synthesize a highly ordered holey carbon nitride material with excess nitrogen atoms for a sustainable solar H(2)evolution. Herein, we report the development of directed highly ordered nitrogen-rich honeycomb-like mesoporous carbon nitride nanosheets by using a novel synthetic approach for this purpose. The unique formation route, surface structure and charge carrier dynamics of the two dimensional holey nanosheets are comprehensively monitored and confirmed by SAXS, HRTEM, AFM, BET, XPS and TRPL analyses. Non-stoichiometric high nitrogen content mesoporous nanosheets with the final stoichiometry of g-C(3)N(4.5)acquiring a high specific surface area (382 m(2)g(-1)), remarkable pore size (7.2 nm) and sheet thickness similar to 5-6 nm are realized in this first report. This elegant material possesses unique low band-gap energy (2.42 eV). Remarkably, the as-synthesized g-C(3)N(4.5)NSs exhibit a record high photocatalytic H(2)evolution rate of 8180 mu mol g(-1)h(-1)under the present light irradiation (420 <=lambda <= 510 nm) condition. The apparent quantum efficiency is found to be as high as 27.14% at 420 nm and retains its photocatalytic activity for longer consecutive catalytic cycles. Bigger pore size and pore volume, and thin walls leading to shortening of the path length of exciton pairs, efficient charge separation and the prolonged average life time of the charge carriers, and lone electron pairs associated with the excess nitrogen content are found to be the reasons behind the excellent visible light driven water splitting reaction.

One-dimensional multichannel g-C3N4.7 nanostructure realizing an efficient photocatalytic hydrogen evolution reaction and its theoretical investigations - Antil, Bindu; Kumar, Lakshya; Ranjan, Ravi; Shenoy, Sulakshana; Tarafder, Kartick; Gopinath, Chinnakonda S.; Deka, Sasanka (ACS Applied Energy Materials, 2021)
The emerging metal-free carbon nitride (C3N4) offers prominent possibilities for realizing the highly effective hydrogen evolution reaction (HER). However, its poor surface conductivity and insufficient catalytic sites hinder the HER performance. Herein, a one-dimensional vermicular rope-like graphitic carbon nitride nanostructure is demonstrated that consists of multichannel tubular pores and high nitrogen content, which is fabricated through a cost-effective approach having the final stoichiometry g-C3N4.7 for HER application. The present g-C3N4.7 is unique owing to the presence of abundant channels for the diffusion process, modulated surface chemistry with rich- electroactive sites from N-electron lone pairs, greatly reduced recombination rate of photoexcited exciton pairs, and a high donor concentration (4.26 x 10(17) cm(3)). The catalyst offers a visible-light-driven photocatalytic H-2 evolution rate as high as 4910 mu mol h(-1)g(-1) with an apparent quantum yield of 14.07% at band gap absorption (2.59 eV, 479 nm) under 7.68 mW cm(-2) illumination. The number of hydrogen gas molecules produced is 1.307 x 10(15) s(-1) cm(-2), which remained constant for a minimum of 18 h of repeated cycling in the HER without any degradation of the catalyst. In density functional theory calculations, a significant change in the band offset is observed due to N doping into the system in favor of electron catalysis. The theoretical band gap of a monolayer of g-C3N4.7 was enormously reduced because of the presence of additional densities of states from the doped N atom inside the band gap. These impurity or donor bands are formed inside the band gap region, which ultimately enhance the hydrogen ion reduction reaction enormously.
Keywords: carbon nitride; Density functional theory; hydrogen evolution reaction; nitrogen-rich; Photocatalyst